Untargeted metabolomics of pulmonary tuberculosis patient serum reveals potential prognostic markers of both latent infection and outcome - Wang, Xuezhi; Wu, Zhuhua; Zeng, Jincheng; Zhao, Yuchuan; Zhang, Chenchen; Yu, Meiling; Wang, Wei; Chen, Xunxun; Chen, Liang; Wang, Jiawen; Xu, Liuyue; Zhou, Jie; et al. (Frontiers in Public Health, 2022)
Currently, there are no particularly effective biomarkers to distinguish between latent tuberculosis infection (LTBI) and active pulmonary tuberculosis (PTB), as well as to evaluate the outcome of TB treatment. In this study, we have characterized the changes of the serum metabolic profiles caused by Mycobacterium tuberculosis (Mtb) infection and standard anti-TB treatment with isoniazid-rifampin-pyrazinamide-ethambutol (HRZE) using GC-MS and LC-MS/MS. Seven metabolites, including 3-oxopalmitic acid, akeboside ste, sulfolithocholic acid, 2-decylfuran, (4,8,8-trimethyldecahydro-1,4-methanoazulen-9-yl)methanol, d-(+)-camphor, and 2-methylaminoadenosine, were identified to have significantly higher levels in LTBI and untreated PTB patients (T0) than those in uninfected healthy controls (Un). Among them, akeboside Ste and sulfolithocholic acid were significantly decreased in PTB patients with 2-month HRZE (T2) and cured PTB patients with 2-month HRZE followed with 4-month isoniazid-rifampin (HR) (T6). Receiver operator characteristic curve analysis revealed that the combined diagnostic model showed excellent performance for distinguishing LT from T0 and Un. By analyzing the biochemical and disease-related pathways, we observed the differential metabolites in serum of LTBI or TB patients, compared to healthy controls, were mainly involved in glutathione metabolism, ascorbate, and aldarate metabolism, and porphyrin and chlorophyll metabolism. The metabolites with significant difference between T0 group and T6 group were mainly enriched in niacin and nicotinamide metabolism. Our study provided more detailed experimental data for developing laboratory standards for evaluating LTBI and cured PTB.